Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1111/j.1469-7793.2000.t01-1-00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Two mechanisms of genistein inhibition of cystic fibrosis transmembrane conductance regulator Cl channels expressed in murine cell line

Abstract: The isoflavone genistein may either stimulate or inhibit cystic fibrosis transmembrane conductance regulator (CFTR) Cl− channels. To investigate how genistein inhibits CFTR, we studied CFTR Cl− channels in excised inside‐out membrane patches from cells expressing wild‐type human CFTR. Addition of genistein (100 μM) to the intracellular solution caused a small decrease in single‐channel current amplitude (i), but a large reduction in open probability (Po). Single‐channel analysis of channel block suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(115 citation statements)
references
References 49 publications
(109 reference statements)
4
110
1
Order By: Relevance
“…To investigate whether phloxine B inhibition of CFTR was voltagedependent and enhanced when the external Cl Ϫ concentration was reduced, we used voltage ramp protocols to acquire macroscopic current-voltage (I-V) relationships as previously described (31). Basal currents recorded before the addition of PKA and ATP were subtracted from those recorded in the absence and presence of phloxine B to determine the effect of phloxine B on CFTR Cl Ϫ currents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate whether phloxine B inhibition of CFTR was voltagedependent and enhanced when the external Cl Ϫ concentration was reduced, we used voltage ramp protocols to acquire macroscopic current-voltage (I-V) relationships as previously described (31). Basal currents recorded before the addition of PKA and ATP were subtracted from those recorded in the absence and presence of phloxine B to determine the effect of phloxine B on CFTR Cl Ϫ currents.…”
Section: Methodsmentioning
confidence: 99%
“…For open probability (P o ) and burst analyses, lists of open-and closed-times were created and analyzed as previously described (31). Burst analysis was performed as described by Carson et al (33), using a t c (the time that separates interburst closures from intraburst closures) of 15 ms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean burst duration (MBD or T MBD ) and open probability within a burst (P o(burst) ) were determined directly from experimental data using pCLAMP software. P o was calculated from open and closed times as described (23). However, for G551D and G1349D, because the number of active channels in a membrane patch was unknown, we measured NP o instead of P o .…”
Section: Cftr CLmentioning
confidence: 99%
“…However, its mechanism of action is distinct from other allosteric inhibitors (e.g. genistein) 113,114 that interfere with the control of CFTR gating by ATP-driven NBD dimerisation by competing with ATP for binding to ATP-binding site 2. First, Kopeikin et al 107 demonstrated that CFTR inhibition by CFTR inh -172 occurs from either the open or closed state and does not involve disassembly of the NBD dimer, but instead is reminiscent of the inactivation mechanism of voltage-gated cation channels.…”
Section: Cftr Inhibitors and Secretory Diarrhoeamentioning
confidence: 99%